Study on the Making of Fermented Taro Crackers - Ridhani Agustia; Zulkifli Lubis; Era Yusraini (Universitas Sumatera Utara, 2016)
In the beginning fermented taro tuber is made to take advantage of the abundant of fresh taro. Taro tuber is used in particular as a source of carbohydrate. This study was conducted to find a ratio of tapioca starch with wheat flour and concentration of fermented taro tubers to produce the best crackers. This research used completely randomized design with two factors, namely the ratio of tapioca starch to wheat flour (K): (100%: 0%, 90: 10%, 80%: 20%, and 70%: 30%) and the concentration of fermented taro (D): (10%, 20%, 30% and 40%). Parameters analyzed were moisture content, ash content, nitrogen content, the volume of development and the organoleptic value (color, aroma, flavor and texture). The results showed that the ratio of tapioca starch and wheat flour gave highly significant effect on water content, ash content, nitrogen content, the volume of development, the value of hedonic flavor and the value of hedonic texture (after frying) and gave a significant effect on the value hedonic color (after frying) and gave no significant effect on the value of hedonic color, hedonic aroma, score aroma (before frying), hedonic aroma, score flavor and score texture (after frying). Concentration of fermented taro bulbs gave highly significant effect on all parameters except the volume development which significant. Interaction between the ratio of tapioca starch to flour and fermented taro root concentration gives highly significant effect on water content, ash content and hedonic flavor. The best crackers fermented taro tubers based on a ratio of tapioca and wheat flour was 100:0 (K1) and the concentration of fermented taro tuber was 20% (D2). Keywords: Crackers, fermented taro roots, tapioca starch, wheat flour.